Transforming Students’ Global Knowledge and Perspectives through International Service-Learning (ISL): How U.S. University Agriculture Students Made Sense of their Lived Experiences Over Time - Richie Roberts; M. Craig Edwards (Journal of International Agricultural and Extension Education, 2016)
University agriculture students are failing in terms of their general global knowledge. As such, the need exists to examine instructional techniques that may assist in overcoming this deficiency. One such approach is international service-learning (ISL). The purpose of the current study, therefore, was to explore the lived experiences of university agriculture students who participated in an ISL opportunity to Uganda, which was partially funded by a grant from the U.S. Department of State. The essence of participants’ lived experiences is best described as a transformative shift in their global knowledge and perspectives. The processes that foregrounded this shift are described through six themes of meaning: (a) contextual border crossing; (b) dissonance; (c) personalizing; (d) processing; (e) connecting; and (f) sustained relationships. Findings suggest students’ perspectives could be modified through ISL. Using Kiely’s (2005) transformative learning model for service-learning (TLMSL), recommendations are offered for research, theory-building, and practice.
Keywords: global perspectives; international service-learning; Uganda; U.S. university students